Disseminated Tuberculosis During the Course of Behçet’s Disease: A Case Report - İbak GÖNEN and Mustafa ÖZŞAHİN and Mustafa YILDIRIM and Davut ÖZDEMİR and Leyla YILMAZ AYDIN and Ali KUTLUCAN and Hakan TURAN and Ahmet ŞAHİN and; zan BÜYÜKKAYA6 (Archives of Rheumatology, 2012)
In this article, a 22 year-old male with disseminated tuberculosis during the course of Behçet’s disease who was admitted with the complaints of fever, headache and fatigue was presented. The initial diagnosis was neuro- Behçet’s syndrome. Tuberculosis during the course of rheumatic diseases are often associated with the use of TNF-alpha blockers. In our case, the patient experienced severe disseminated tuberculosis, despite being TNFalpha blocker-naive. To the best of our knowledge, this is the first case of tuberculosis with such a disseminated course developed in a patient with Behçet’s disease who received conventional immunosuppressive treatment.